2022
DOI: 10.1159/000527691
|View full text |Cite
|
Sign up to set email alerts
|

The EASO New Investigator Award in Clinical Research 2021: Role of Chronotype in Obesity

Abstract: Background: Chronotype is the expression of the timing of circadian rhythmicity of a subject, and three categories of chronotype have been identified: morning, evening and intermediate chronotype. Subjects with morning chronotype prefer to carry out most of their daily activities in the morning while subjects with evening chronotype perform most of their daily activities in the second half of the day. Intermediate chronotype is in an intermediate position between the above reported categories. Recently evening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
0
2
0
1
Order By: Relevance
“…Previous studies reported that individuals with a nighttype chronotype are at a higher risk of obesity [28]. However, the mechanisms linking chronotype with obesity have not been clarified to date.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported that individuals with a nighttype chronotype are at a higher risk of obesity [28]. However, the mechanisms linking chronotype with obesity have not been clarified to date.…”
Section: Discussionmentioning
confidence: 98%
“…We observed associations between these genes and vision-related traits (macular thickness and myopia) and oncology (lung cancer independent of smoking and adverse response to chemotherapy in breast cancer). Like alcohol, links between breast cancer and chronotype may be mediated by cardiometabolic factors already discussed [64]. Taking diurnal preference into account has been suggested as a low-cost adjunctive consideration when planning radiooncology treatments [65].…”
Section: Discussionmentioning
confidence: 99%
“…Akşamcıl tipe sahip olma; bireylerin beslenme durumunu, uyku kalitesini, fiziksel aktivitesini olumsuz etkilediği için obezite durumu ile ilişkilendirilmektedir (31). Ancak yapılan bazı çalışmalarda tüm kronotipler ile vücut ağırlığı ve BKİ arasında anlamlı bir ilişki belirlenmemişken (7,32) bazı çalışmalarda ise sadece akşamcıl tipe sahip olma ile bu olgular arasında anlamlı bir ilişkili bulunmuştur (33,34).…”
Section: Discussionunclassified